BUMDes dan Dampaknya Terhadap Ekonomi Masyarakat - Azmi Hibatullah; Asep Shodiqin (Tamkin: Jurnal Pengembangan Masyarakat Islam, 2021)
This study aims to analyze as well as objectively determine the impact of the existence of BUMDes in Sukamaju Village in improving the economy of the community so that the existence of BUMDes can be felt by the community. Then, community participation in welcoming the program owned by BUMDes Sukamaju Village itself. In the context of the framework of thought, one of the theories used is the theory of impact according to Gorys Often which includes influence, social strata and administrative positions where all of these elements will provide social effects to the community that are able to cause changes in both positive and negative directions. The results of the study show that BUMDes has provided various impacts of economic change to the community. There is an increase in the level of the economy in rural communities, such as sewing business, provision of entrepreneurship training and community distribution to potential-based private companies as well as increasing community participation in every economic and social activity initiated by BUMDes. In general, the conclusion is that the presence of BUMDes in Sukamaju village has had a positive impact on the surrounding community.